2004
DOI: 10.1002/clc.4960270504
|View full text |Cite
|
Sign up to set email alerts
|

Importance of a history of hypertension for the prognosis after acute myocardial infarction‐‐‐for the bucindolol evaluation in acute myocardial infarction trial (BEAT) study group

Abstract: SummaryBackground: Arterial hypertension is a major risk factor for cardiovascular events. The prognosis for hypertensive patients after acute myocardial infarction (MI) is uncertain because of the sparse and somewhat contradictionary data.Hypothesis: Our study aimed to investigate the importance of hypertension to prognosis after an MI in patients receiving contemporary medical therapy.Methods: We performed a retrospective study using a large register from the Bucindolol Evaluation in Acute myocardial infarct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 32 publications
1
7
0
Order By: Relevance
“…The HTrelated results of this study were therefore expected, as similar results regarding early (b 30 days) mortality have been seen in previous studies of non-specific acute MI [23] and non-STEMI [9,10,24] and also in patients with coexisting DM [25].…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…The HTrelated results of this study were therefore expected, as similar results regarding early (b 30 days) mortality have been seen in previous studies of non-specific acute MI [23] and non-STEMI [9,10,24] and also in patients with coexisting DM [25].…”
Section: Discussionsupporting
confidence: 76%
“…Although the data from the literature are somewhat contradictory [9], previous studies have shown that hypertensive patients, especially younger individuals [11], run an increased risk of cardiovascular morbidity [21,22] and have a poorer outcome after an acute coronary event [12]. The HTrelated results of this study were therefore expected, as similar results regarding early (b 30 days) mortality have been seen in previous studies of non-specific acute MI [23] and non-STEMI [9,10,24] and also in patients with coexisting DM [25].…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…The literature on the effect of hypertension on short-and long-term mortality is conflicting; many studies have claimed a deleterious effect of hypertension in ACS with an increasing risk of death [11][12][13] while others, including the current study and Gulf RACE-1, failed to show this [6][7][8][9][11][12][13][14][15][16][17][18][19]. Other investigators reported better outcomes in hypertensive patients presenting with ACS [20,21].…”
Section: Discussionmentioning
confidence: 43%
“…Those who had hyperglycemia and DM were 29%. The incidence of hyperglycemia with DM varies in different studies between 23%–41% 12,13. Thirty two percent had history of hypertension, which is higher than those previously reported (28% and 25%) in other studies, respectively 14,15…”
Section: Discussionmentioning
confidence: 70%